Effect of radio frequency heating on yoghurt - I. Technological applicability, shelf-life and sensorial quality - Siefarth, Caroline; Tran, Thi Bich Thao; Mittermaier, Peter; Pfeiffer, Thomas; Büttner, Andrea (Foods, 2014)
Radio frequency (RF) heating was applied to stirred yoghurt after culturing in order to enhance the shelf-life and thereby meet industrial demands in countries where the distribution cold chain cannot be implicitly guaranteed. In parallel, a convectional (CV) heating process was also tested. In order to meet consumers’ expectations with regard to texture and sensory properties, the yoghurts were heated to different temperatures (58, 65 and 72 °C). This second part of our feasibility study focused on the changes in microstructure and texture caused by post-fermentative heat treatment. It was shown that there were always microstructural changes with additional heat treatment. Compared to the dense and compact casein network in the stirred reference yoghurt, network contractions and further protein aggregation were observed after heat treatment, while at the same time larger pore geometries were detected. The changes in microstructure as well as other physical and sensorial texture properties (syneresis, hardness, cohesiveness, gumminess, apparent viscosity, G’, G’’, homogeneity) were in good agreement with the temperature and time of the heat treatment (thermal stress). The RF heated products were found to be very similar to the stirred reference yoghurt, showing potential for further industrial development such as novel heating strategies to obtain products with prolonged shelf-life.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.effect_7
Keywords: heating; microstructure; radio frequency; cryo-SEM; texture; yoghurt